A necessary condition to test the minimality of generalized linear sequential machines using the theory of near-semirings - Krishna, K.V.; Chatterjee, N. (Algebra and Discrete Mathematics, 2005)
In this work first we study the properties of nearsemirings to introduce an α-radical. Then we observe the role of near-semirings in generalized linear sequential machines, and we test the minimality through the radical.